The emerging mechanisms and functions of microautophagy - Wang, Liming; Klionsky, Daniel J.; Shen, Han-Ming (Nature reviews. Molecular cell biology, 2023)
‘Autophagy’ refers to an evolutionarily conserved process through which cellular contents, such as damaged organelles and protein aggregates, are delivered to lysosomes for degradation. Different forms of autophagy have been described on the basis of the nature of the cargoes and the means used to deliver them to lysosomes. At present, the prevailing categories of autophagy in mammalian cells are macroautophagy, microautophagy and chaperone-mediated autophagy. The molecular mechanisms and biological functions of macroautophagy and chaperone-mediated autophagy have been extensively studied, but microautophagy has received much less attention. In recent years, there has been a growth in research on microautophagy, first in yeast and then in mammalian cells. Here we review this form of autophagy, focusing on selective forms of microautophagy. We also discuss the upstream regulatory mechanisms, the crosstalk between macroautophagy and microautophagy, and the functional implications of microautophagy in diseases such as cancer and neurodegenerative disorders in humans. Future research into microautophagy will provide opportunities to develop novel interventional strategies for autophagy- and lysosome-related diseases. Microautophagy involves direct engulfment of cytoplasmic components, including proteins and organelles, by lysosomes and late endosomes for degradation. Although it is one of three main types of autophagy — along with macroautophagy and chaperone-mediated autophagy — its mechanisms and physiological roles have only recently begun to emerge.